Strategy for Improving Marketing Performance of Sri Rejeki Retail Store Kediri Using SWOT Analysis - Delima, Elsa Sindi; Helilusiatiningsih, Nunuk; Saptaria, Lina (Fakultas Ekonomi Universitas Kadiri, 2025)
The selection of a competitive strategy greatly determines the marketing performance of a retail business. This research aims to determine the competitive strategy of the Sri Rejeki Kediri Retail Store in improving marketing performance based on SWOT analysis. This type of research is descriptive qualitative. Data collection methods through observation, interviews, documentation. The results of the SWOT analysis show that the total strength score is 1.672, weaknesses are 1.12, opportunities are 2.43, and threats are 1.2. The total average score on the IFAS matrix is 2.80 while the EFAS matrix is 3.36. These results show that the company's position based on the IE matrix is in quadrant II, which shows that the store has considerable strengths and opportunities to improve marketing performance. The results of this analysis are useful for managers and shop owners to formulate competitive strategies by taking into account the strengths and opportunities that have been identified.